The Psychometric Properties of the Frost Multidimensional Perfectionism Scale – Brief - Woodfin, Vivian; Binder, Per-Einar; Molde, Helge (Frontiers in Psychology, 2020)
Previous psychometric analyses of the Frost Multidimensional Perfectionism Scale and the abbreviated version (FMPS–Brief) have resulted in inconsistent findings regarding the scale’s bidimensionality or unidimensionality. Different studies evaluating the scale with different statistical analyses and comparative samples report different results and recommendations. This study assessed the FMPS-B’s psychometric properties by conducting both confirmatory factor analysis (CFA) and pure bifactor modeling in order to address previous findings and guide future use of the scale. The results indicate that the two-factor model is the best fit. Going forward, the FMPS-B’s subfactors “strivings” and “evaluative concerns” may be studied separately. Implications for future research and challenges in bifactor modeling are discussed.